2018
DOI: 10.2147/ndt.s169099
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates the propofol-induced long-term neurotoxicity in the developing brain of rats by enhancing the PI3K/Akt signaling pathway

Abstract: BackgroundPropofol induces short- and long-term neurotoxicity. Our previous study showed that dexmedetomidine (Dex) can attenuate the propofol-induced acute neurotoxicity in rodents by enhancing the PI3K/Akt signaling. However, whether treatment of young rats with Dex could protect them from long-term neurotoxicity induced by propofol is unclear.Materials and methodsSeven-day-old male Sprague Dawley rats were randomized and injected intraperitoneally with saline (100 μL, NS), propofol (100 mg/kg), Dex (75 μg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…This is in agreement with others, where a single injection of propofol (60 mg/kg), administered at the neonatal peak period of CNS development, was insufficient to cause cognitive dysfunction of juvenile mice [10]. However, Xiao et al [11] found that 9 week old rats showed aberrant neurological deficits after receiving the 100 mg/kg propofol (50 mg/kg, twice) at the neonatal period. The discrepant reason may be due to their different drug regimen, which somehow decreased number of neurocytes, self-renewal and differentiation capacity of neural stem cells during the period of mature brains.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with others, where a single injection of propofol (60 mg/kg), administered at the neonatal peak period of CNS development, was insufficient to cause cognitive dysfunction of juvenile mice [10]. However, Xiao et al [11] found that 9 week old rats showed aberrant neurological deficits after receiving the 100 mg/kg propofol (50 mg/kg, twice) at the neonatal period. The discrepant reason may be due to their different drug regimen, which somehow decreased number of neurocytes, self-renewal and differentiation capacity of neural stem cells during the period of mature brains.…”
Section: Discussionsupporting
confidence: 90%
“…These results were consistent with previous similar studies (Li et al, 2014; Sanders et al, 2010, 2009), though inconsistent with others (Lee et al, 2017; Perez‐Zoghbi et al, 2017). In previous studies, DEX ameliorated the neuroapoptosis and cognitive dysfunction induced by exposure of the developing brain to isoflurane (Li et al, 2014; Sanders et al, 2010, 2009), sevoflurane (Perez‐Zoghbi et al, 2017), and propofol (Lv et al, 2017; Wang et al, 2016; Xiao et al, 2018). Sanders et.…”
Section: Discussionmentioning
confidence: 91%
“…Based on a previous study, DEX may attenuate the reduction in the expression of anti‐apoptotic signaling pathways mediated by Bcl‐2 and phosphor‐ERK1/2 induced by isoflurane anesthesia, in a similar manner to that of neonatal brain injury (Li et al, 2014). Moreover, DEX has anti‐apoptotic effects (Engelhard et al, 2002), decreases caspase‐3 elevation (Dahmani et al, 2005; Eser et al, 2008) and attenuates the activation of the PI3k/Akt/ glycogen synthase kinase (GSK)3beta pathway in propofol‐induced neuroapoptosis (Lv et al, 2017; Wang et al, 2016; Xiao et al, 2018). Further research is warranted in order to ascertain the precise neuroprotective mechanisms of DEX against neural toxicity induced by anesthesia exposure in the neonatal brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on accumulating evidence, propofol may induce developmental neurotoxicity, raising serious concerns regarding the use of propofol anesthesia in pediatric patients 57. Dexmedetomidine, a highly selective α2-adrenergic agonist, exerts a neuroprotective effect on propofol-induced neurotoxicity,810 but the associated mechanisms have not yet been fully clarified. The neuroprotective effects of dexmedetomidine are mediated by its binding to imidazoline I1 receptors and modulating histone acetylation via Erk1/2 pathways 1113.…”
Section: Introductionmentioning
confidence: 99%